Analisis Penggunaan Sistem Parabolic Trough Collector pada Bypass High Pressure Heater PLTU 600 MW - Farhansyah, Farhansyah; Alvera Apridalianti Melkias; Ignatius Riyadi Mardiyanto (SURYA TEKNIKA, 2024)
The regenerative process involves heating the feedwater out of the condenser using residual steam or extraction from the steam turbine and then pumping it back into the boiler. To achieve the greenhouse gas emission reduction target set by the Government of the Republic of Indonesia, power plant managers need to consider strategies to reduce these emissions. One strategy that can be taken is to harness solar energy through parabolic trough type solar collectors. In PLTUXYZ, the design of a parabolic trough type solar collector is carried out on bypasses HPH 6 through HPH 8 using system advisory model and gatecycle software. The design results show that the existence of this solar collector has the potential to reduce coal use by 9.33 tons/hour under optimal solar conditions, with coal savings reaching 4,143.3 tons of coal for USD 380,231.30/year.